PEMANFAATAN MEDIA SOSIAL INSTAGRAM SEBAGAI MEDIA PEMBELAJARAN MATERI PEMASARAN PRODUK MATA PELAJARAN PRODUK KREATIF DAN KEWIRAUSAHAAN KELAS XII MULTIMEDIA SMKN 1 SURABAYA - Karmila Ridha Rahma; Hari Sugiharto Setyaedhi (Universitas Negeri Surabaya, 2023)
The purpose of this study was to find out the use of social media Instagram as a learning medium for product marketing materials in the multimedia department of SMKN 1 Surabaya. The research method used is a qualitative method, while the research design used is a case study. Methods of data collection using observation, interviews, and documentation studies. To test the validity of the data using the credibility test (Internal Validity) and Transferability test (External Validity). The subjects in this study were students of class XII Multimedia. Data collection using interviews, observation, and documentation was used to determine the characteristics of students, knowledge of sources related to Instagram social media, and the number of project assignments. The main results of this study indicate that students can utilize Instagram social media as a learning medium in creative and entrepreneurship product subjects to carry out product marketing and promotion, providing the latest references to students can provide stimulation their creativity, in the implications of working on projects using Project Based Learning learning model.